Inclusive Communication Model: Phenomenological Workplace Experiences of Deaf Workers in Pontianak - Saputra, Dimas; Rosnani, Titik; Jaya, Arman; Fahruna, Yulyanti; Marumpe, Dody Pratama (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The findings reveal an "Adaptive Total Communication" ecosystem integrating BISINDO and visual cues. A key discovery is "Inverse Integration," where hearing workers voluntarily adopt silence protocols to align with deaf visual norms. However, full inclusion is still hindered by linguistic dissonance and the impracticality of digital tools in high-pressure settings. Theoretically, this study extends Co-Cultural Theory by showing communicative adaptation shifting from the marginalized to the majority. Practically, it proposes a "Community-Based Adaptive System" prioritizing human infrastructure such as mentors and low-cost physical modifications like light signals. These results provide a strategic roadmap for micro-enterprises to foster independent, inclusive environments without relying on expensive technology, ensuring sustainable accessibility in dynamic work settings.